2016
DOI: 10.4137/ebo.s38085
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Evolution of Disease Resistance Genes in Barley (Hordeum vulgare L.)

Abstract: Plant disease resistance genes (R-genes) play a critical role in the defense response to pathogens. Barley is one of the most important cereal crops, having a genome recently made available, for which the diversity and evolution of R-genes are not well understood. The main objectives of this research were to conduct a genome-wide identification of barley Coiled-coil, Nucleotide-binding site, Leucine-rich repeat (CNL) genes and elucidate their evolutionary history. We employed a Hidden Markov Model using 52 Ara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
21
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 98 publications
7
21
1
1
Order By: Relevance
“…We found a high frequency of leucine-rich repeat, NB-ARC, and serine/threonine-protein kinase-like genes as putative candidate genes in rust resistance QTL intervals of HEB-25. This finding is in agreement with the important role of those gene families, known as resistance gene analogs (RGAs), in various defence reactions of plants against pathogens [ 101 , 102 ]. Based on this study the definition of a single candidate gene responsible for the detected QTL effect is not feasible.…”
Section: Discussionsupporting
confidence: 82%
“…We found a high frequency of leucine-rich repeat, NB-ARC, and serine/threonine-protein kinase-like genes as putative candidate genes in rust resistance QTL intervals of HEB-25. This finding is in agreement with the important role of those gene families, known as resistance gene analogs (RGAs), in various defence reactions of plants against pathogens [ 101 , 102 ]. Based on this study the definition of a single candidate gene responsible for the detected QTL effect is not feasible.…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, proteins lacking CC or LRR domains may also contribute to resistance responses, especially those with additional domains that are involved in signaling (Baggs et al, 2017). The distribution of NBAC genes across wheat chromosomes concurs with previous studies in barley and foxtail millet, where R genes were also found in clusters in extrapericentromeric regions of chromosomes (Andersen et al, 2016;Andersen and Nepal, 2017). Unequal crossing over between chromosomes as a mechanism for duplication likely explains the formation of these clusters, which then allows for their diversification.…”
Section: Discussionsupporting
confidence: 87%
“…The combination of different resistance genes is generally considered to be a successful strategy to enhance resistance. In barley, a considerable number of resistance genes have been described (Andersen et al ., ; Seeholzer et al ., ). The most well‐known and cloned major barley resistance genes that act efficiently as single genes are Rpg1 and the Mla alleles (Brueggeman et al ., ; Chelkowski et al ., ).…”
Section: Discussionmentioning
confidence: 99%